Printable self-adhesive elastic conductive ink as well as preparation method and application thereof
Through the combination of thermoplastic elastomer, interface reinforcer and adhesive, elastic conductive ink with high adhesion and low diffusion is prepared, which solves the problem of poor adaptability of conductive ink on complex substrates and realizes the High precision printing and power stability.
Patent Information
- Application Number
- CN202411167408.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-01-10
AI Technical Summary
Existing conductive inks have poor adaptability on complex substrates and cannot have both electrical and mechanical stability, especially on rough or porous substrates to achieve high precision and high throughput printing difficulties.
Use thermoplastic elastomers, interface reinforcers and adhesives to form elastic conductive inks with self-adhesion, high permeability and low diffusion, and promote conductive fillers through block copolymers, surfactants and polyester elastomers. The uniform dispersion and interface stability are suitable for smooth and rough substrates.
It realizes high-precision printing on different substrates, has good electromechanical stability and wear resistance, can maintain low resistance under large tensile strain, and is suitable for daily deformation and repeated use of flexible electronic devices.
Smart Images

Figure CN119286306A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of conductive ink, and in particular relates to a printable self-adhesive elastic conductive ink and a preparation method and application thereof. Background Art
[0002] Printable flexible stretchable electronics have the advantages of precise design, large-scale and efficient production, and have important application potential in the fields of health monitoring, electronic skin and soft robots. During the use of flexible printed electronics, the substrate is subjected to complex mechanical forces, and the corresponding ink is also subjected to mechanical deformation such as stretching, compression and bending. In addition, due to the large roughness and microstructure differences on the surfaces of various substrates, the interface stability between the ink and the substrate and the electromechanical durability of the corresponding device are seriously affected. The current various conductive inks usually require substrate pretreatment to reduce the surface roughness or regulate the surface wettability before they can meet the printing requirements, which increases the processing complexity and cost and limits the applicability of diversified substrates. Therefore, it is of great significance to prepare an elastic conductive ink that meets a variety of processing strategies and usage requirements and can be directly printed / printed without substrate pretreatment. It can significantly provide diversified flexible substrate adaptability, construct high-performance conductive patterns of electromechanics, and promote the development of the field in the direction of high efficiency and low cost.
[0003] The rapid development of highly integrated and miniaturized flexible electronics has put forward higher demands for high-precision printing / printing of conductive inks on substrates with different surface roughness. Generally speaking, there is a larger contact area between a smooth substrate and the printed ink, so the ink adhesion is better and high-precision printing is relatively easy to achieve. However, to achieve high-precision printing of conductive inks on rough substrates, especially porous substrates, it is necessary not only to improve the permeability and adhesion of the ink, but also to reduce the lateral diffusion of the ink to achieve a continuous and stable conductive path. At present, there is a lack of a conductive ink with self-adhesive elastic characteristics to meet the needs of high-precision and high-throughput printing on complex substrates. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a printable self-adhesive elastic conductive ink and a preparation method and application thereof, and in particular to a printable self-adhesive elastic conductive ink and a preparation method thereof that is stable in conductivity under large strain, so as to overcome the poor adaptability of conductive inks in the prior art to complex substrates (such as rough or porous substrates such as fabrics) and the inability to have both electrical and mechanical stability. The ink has self-adhesion, high permeability and low diffusivity, and can be suitable for printing on various smooth substrates and fabric substrates with different tissue structures.
[0005] The present invention provides an elastic conductive ink, which comprises the following components in parts by weight:
[0006]
[0007] The thermoplastic elastomer is a block copolymer; the interface enhancer is a surfactant and a polyester elastomer composite; the adhesive is a polyacrylate;
[0008] The block copolymer includes one or more triblock copolymers such as polystyrene-polybutadiene-polystyrene block copolymer, polystyrene-polyisoprene-polystyrene block copolymer, polystyrene-ethylene-butylene-polystyrene block copolymer, etc.; the surfactant includes one or more silane coupling agents and titanate coupling agents; the polyester elastomer includes one or more ethylene-vinyl acetate copolymer (vinyl acetate content is between 40% and 70%) and ethylene-methyl methacrylate copolymer (methyl methacrylate content is between 10% and 20%).
[0009] Preferably, the mass ratio of the surfactant to the polyester elastomer in the interface enhancer is 10 to 5:1.
[0010] The silane coupling agent is one or more of KH550, KH560, KH570 and KH590; the titanate coupling agent is one or more of isopropyl tri(dioctylphosphino)titanate and isopropyl tri(dodecylbenzenesulfonyl)titanate.
[0011] More preferably, the interface enhancer is a composite of a silane coupling agent (KH570) and a polyester elastomer, and the interface enhancer is used to bridge the rigid conductive filler (such as silver flakes) and the thermoplastic elastomer to promote uniform dispersion of the rigid conductive filler silver flakes in the elastomer.
[0012] The adhesive comprises one or more of polyethyl acrylate, polybutyl acrylate and poly(butyl acrylate-styrene);
[0013] Preferably, the adhesive is polybutyl acrylate.
[0014] Preferably, the conductive filler is composed of rigid conductive filler and flexible conductive filler.
[0015] Preferably, the mass ratio of the rigid conductive filler to the flexible conductive filler is 10:20 to 10:40.
[0016] Preferably, the rigid conductive filler includes one or more of metal micro-nano particles, metal nanowires, metal micro-nano sheets, carbon-based micro-nano conductive materials, modified carbon-based or metal micro-nano conductive materials, and transition metal micro-nano conductive materials; the flexible conductive filler includes one or more of ionic liquids, liquid metal gallium, liquid alloy gallium-indium alloy, gallium-indium-tin alloy, and liquid metal modifiers.
[0017] Preferably, the metal nanoparticles include one or more of gold micro-nanoparticles, silver micro-nanoparticles, and copper micro-nanoparticles; the metal nanowires include one or more of gold nanowires, silver nanowires, and copper nanowires; the metal micro-nanosheets include one or more of gold micro-nanosheets, silver micro-nanosheets, and copper micro-nanosheets; the carbon-based micro-nano conductive materials include one or more of carbon black micro-nano particles, carbon nanotubes, graphene, and MXene.
[0018] Preferably, the rigid conductive filler is silver micro-nanosheets; the flexible conductive filler is a liquid alloy or gallium-indium alloy microsphere that has been subjected to high-speed shear dispersion treatment or ultrasonic treatment.
[0019] More preferably, the average particle size of the silver micro-nano sheets is 0.1 to 100 μm; the average particle size of the gallium-indium alloy microspheres is 0.1 to 100 μm.
[0020] The high-speed shearing and dispersing treatment time is 1 min to 30 min, the rotation speed is 5000 r / min to 25000 r / min; the ultrasonic treatment time is 1 min to 2 h, the power is 50 W to 500 W.
[0021] The present invention provides a printing and / or printing material, wherein the material is a printing material and / or printing material based on the elastic conductive ink, and the substrate used by the printing and / or printing material is a smooth substrate, or a rough and / or porous substrate.
[0022] The elastic conductive ink is suitable for high-precision printing or printing on a smooth substrate, or a rough and / or porous substrate.
[0023] The smooth substrate includes (polyvinyl chloride, polypropylene, wood board, stainless steel plate, polyimide film, polyethylene terephthalate film, etc.); the rough and / or porous substrate includes (frosted polypropylene, paper, textile fabrics with different organizational structures, etc., including but not limited to plain woven structure, twill woven structure, weft plain knitting, 2×2 double thread structure, non-woven structure and other textile fabrics).
[0024] The present invention provides an elastic conductor, which comprises the elastic conductive ink and an elastic substrate; wherein the elastic conductive ink is cast onto the elastic substrate to obtain the elastic conductor; wherein the elastic substrate comprises the thermoplastic elastomer, an interface enhancer, an adhesive, and a solvent, which are mixed and then solidified to obtain the elastic conductor.
[0025] A method for preparing an elastic conductive ink of the present invention comprises:
[0026] (1) mixing a thermoplastic elastomer, an interfacial enhancer, an adhesive, and a solvent to obtain a mixed solution;
[0027] (2) Dispersing the conductive filler in the mixed solution of step (1), defoaming and removing the residual air, and obtaining elastic conductive ink.
[0028] The solvent in step (1) includes one or more of water, acetone, toluene, chlorobenzene, xylene, tetrahydrofuran, N,N-dimethylformamide, dimethyl sulfoxide, and chloroform.
[0029] The mass percentage of the thermoplastic elastomer in the mixed solution in step (1) is 5% to 30%.
[0030] The step (1) is specifically as follows: the thermoplastic elastomer and the solvent are stirred and evenly dispersed, and then the interface enhancer and the adhesive are added and stirred evenly to obtain a mixed solution; wherein the surfactant in the interface enhancer and the polyester elastomer can be added together or separately.
[0031] The step (2) of dispersing the conductive filler in the mixed solution of step (1) is specifically as follows: firstly dispersing the flexible conductive filler in the mixed solution of step (1), and then adding the rigid conductive filler for dispersion;
[0032] The flexible conductive filler is dispersed in the mixed solution of step (1), wherein the dispersion is performed by stirring for 1 minute to 5 hours;
[0033] Then, a rigid conductive filler is added for dispersion, wherein the dispersion is performed by stirring for 1 minute to 5 hours.
[0034] The defoaming in step (2) is ultrasonic defoaming, wherein the ultrasonic defoaming time is 1 min to 30 min and the power is 100 W to 300 W.
[0035] The present invention provides an application of the elastic conductive ink in the fields of printing / printing electronic devices, human health monitoring, electronic skin, soft robots, human-machine interaction, information transmission, and energy collection and storage.
[0036] Preferably, the applications in the field of information transmission include electrical signal transmission, interaction or information acquisition equipment.
[0037] Preferably, the application in the field of energy collection and storage covers bioenergy, solar energy and ocean energy collection, etc., specifically including flexible printed friction nanogenerators, flexible printed micro supercapacitors and other energy collection and storage devices.
[0038] Preferably, the human health monitoring field includes printed electronics for monitoring information of biological surface secretions and printed electronic devices that can be implanted in the body and have biocompatibility.
[0039] The present invention blends a thermoplastic elastomer, an interface enhancer, and an adhesive, and utilizes the microphase separation "island structure" formed by the three to achieve material stress dispersion and interface adhesion, thereby obtaining a thermoplastic elastomer material with excellent elasticity and adhesion. The amphiphilic surfactant promotes the formation of nanoscale microphase separation. The microphase separation structure not only enhances the mechanical toughness of the elastomer, but also the polyester elastomer and the adhesive can enhance the interaction between ink components through hydrogen bonds, and can also interact with the oxide layer on the surface of the flexible conductive filler, such as the gallium oxide layer and the lubricating layer on the surface of the rigid conductive filler, to promote the conductive filler to be uniformly dispersed in the ink. At the same time, the silane coupling agent inside the interface enhancer is amphiphilic, which further promotes the interface stability between polymer molecules inside the ink and between the polymer and the conductive filler. The preferred thermoplastic elastomer and polyester elastomer themselves have excellent stretchability and certain adhesion. Adding an adhesive further improves the adhesion of the ink. After optimizing the ratio, the ink with excellent elasticity, resilience and adhesion has universal adhesion to various substrates, ensuring that the electrode has good stretchability and resilience after curing, meeting the daily deformation and repeated use requirements of flexible electronic devices. By adjusting the content of block copolymer thermoplastic elastomer, interfacial enhancer, adhesive and conductive filler, the viscosity and rheological properties of the ink can be adjusted to achieve high penetration and low diffusion performance of the ink on rough or porous substrates. When the elastic conductive ink is printed on a fabric substrate, the pores between the yarns and the good "wicking effect" of the yarns themselves can promote the vertical penetration of the ink on the fabric and effectively limit the lateral diffusion of the ink. At the same time, based on the advantages of rapid curing of highly volatile solvents, the high-precision and high-throughput printing / printing of the ink can be improved.
[0040] The present invention utilizes the deformation characteristics of flexible conductive fillers to effectively bridge rigid conductive fillers, thereby improving the electrical stability of the conductive network when deformed; the use of interface enhancers further promotes the dispersibility of the conductive filler in the ink polymer and the interface stability between the two, thereby enhancing the electromechanical stability between the conductive and non-conductive phases. The ink directly forms a highly conductive interface pattern after printing / printing, and can serve electronic devices without other post-processing steps. When subjected to external force, the rigid conductive filler and the flexible conductive filler undergo synchronous oriented movement, while the liquid metal microspheres are broken and released by force, and the displaced rigid conductive path is repaired again, achieving low resistance changes under large tensile strain, and obtaining a printed conductor with dynamically stable conductivity.
[0041] The ink comprises a continuous phase-thermoplastic elastomer matrix, a dispersed phase-conductive filler, an interface enhancer, and an adhesive. The thermoplastic elastomer matrix is composed of a block copolymer, an interface enhancer, and an adhesive, and the conductive filler is composed of a rigid-flexible conductive filler.
[0042] Beneficial Effects
[0043] The present invention utilizes the electromechanical matching effect between thermoplastic elastomers, interfacial enhancers, adhesives and conductive fillers to regulate the adhesion, permeability / diffusivity and rheology of elastic conductive ink, and achieve high electromechanical stability and high substrate adaptability of flexible printed conductors; the ink can be directly printed / printed on various smooth or rough substrates, and is particularly suitable for direct printing / printing of fabric materials with different tissue structures. Typically, the conductive ink has self-adhesion (0.1MPa~2MPa), high permeability and low diffusivity (0%~5%), can be adapted to various substrates for printing / printing, and obtains high electromechanical stability. The printed electrode can maintain extremely low resistance change (R / R0=0~20) under high tensile deformation (500%~1500%), can be printed / printed on fabrics to achieve stretchable conductive fabrics, and has good wear resistance and water washability.
[0044] The invention has simple process, short flow, excellent product performance, is convenient for batch and large-scale production, and has good application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 The present invention can print self-adhesive elastic conductive ink (comparative example), and the effect of adhesive on the adhesion of conductive ink on different substrates;
[0046] Figure 2 Schematic diagram of components of the printable self-adhesive elastic conductive ink (Example 1) of the present invention;
[0047] Figure 3 Adhesion of the printable self-adhesive elastic conductive ink (Example 1) of the present invention on different substrates;
[0048] Figure 4 The elastic conductor prepared by the printable self-adhesive elastic conductive ink (Example 1) of the present invention shows the change of its resistance and stress with strain under uniaxial tension at room temperature;
[0049] Figure 5 Scanning electron microscope images of the upper surface and cross section of an elastic conductor prepared by the printable self-adhesive elastic conductive ink (Example 2) of the present invention;
[0050] Figure 6 Adhesion of the printable self-adhesive elastic conductive ink (Example 2) of the present invention on different substrates;
[0051] Figure 7 The elastic conductor prepared by the printable self-adhesive elastic conductive ink (Example 2) of the present invention shows the change of its resistance and stress with strain under the uniaxial tensile test at room temperature;
[0052] Figure 8The elastic conductor prepared by the printable self-adhesive elastic conductive ink (Example 2) of the present invention is a curve of resistance and stress variation with time under 200% strain cyclic tensile test at room temperature;
[0053] Fig. 9 The present invention can print a polyester knitted fabric electrode prepared by self-adhesive elastic conductive ink (Example 2), and the upper surface is printed with a SEM image of diffusion and cross section;
[0054] Fig.10 Invention printable self-adhesive elastic conductive ink (Example 2) prepared cotton knitted fabric electrode, upper surface printing diffusion and cross-section scanning electron microscope image;
[0055] Fig.11 Adhesion of the printable self-adhesive elastic conductive ink (Example 3) of the present invention on different substrates;
[0056] Fig.12 The elastic conductor prepared by the printable self-adhesive elastic conductive ink (Example 3) of the present invention shows the change of its resistance and stress with strain under the uniaxial tensile test at room temperature;
[0057] Fig.13 Adhesion of the printable self-adhesive elastic conductive ink (Example 4) of the present invention on different substrates;
[0058] Fig.14 The elastic conductor prepared by the printable self-adhesive elastic conductive ink (Example 4) of the present invention shows the change of its resistance and stress with strain under the uniaxial tensile test at room temperature;
[0059] Fig.15 The present invention can print self-adhesive elastic conductive ink (Example 5), and prepare conductive circuits on polyimide films by dispensing printing;
[0060] Fig.16 The present invention can print self-adhesive elastic conductive ink (Example 5) and prepare conductive electrodes on polyester knitted fabric by mask printing. DETAILED DESCRIPTION
[0061] The present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application. Examples and Comparative Examples:
[0062] Ethylene-methyl methacrylate copolymer, wherein the mass percentage of methyl methacrylate is 15%;
[0063] Ethylene-vinyl acetate copolymer, wherein the mass percentage of vinyl acetate accounts for 41%.
[0064] Comparative Example
[0065] In this embodiment, a printable self-adhesive elastic conductive ink is provided, and the preparation method of the conductive ink is as follows: a thermoplastic elastomer solution is prepared according to a polymer mass fraction ratio of 19wt% (mass fraction of polystyrene-polyisoprene-polystyrene block copolymer in toluene solution), 0.4g of polystyrene-polyisoprene-polystyrene block copolymer is weighed, added to a toluene solvent, and magnetically stirred at room temperature at 600rpm for 10h to prepare a thermoplastic elastomer solution. 0.08g of ethylene-methyl methacrylate copolymer and 0.08g of surfactant KH570 are weighed, added to the thermoplastic elastomer solution, and magnetically stirred at room temperature at 600rpm for 2h to obtain an elastomer mixed solution A. On the basis of the elastomer mixed solution A, 0.16g of polybutyl acrylate is added, and the elastomer mixed solution B is obtained after magnetic stirring for 2h. Take 3.2g of gallium indium tin alloy, use a high-speed shear disperser (Scientz S10), and treat it at 10000r / min for 10min to obtain gallium indium tin alloy liquid microspheres with an average particle size of 6μm. The dispersed gallium indium tin alloy liquid microspheres are added to the above-mentioned elastomer mixed solutions A and B respectively, and vortex dispersed for 10min at room temperature to obtain a gallium indium tin alloy liquid microsphere dispersion. Then take 1g of silver nanoparticles (average particle size 200nm) and add them to the above-prepared dispersion respectively. At room temperature, vortex mix and disperse for 20min to obtain a uniformly dispersed composite conductive filler dispersion. After defoaming in a water bath ultrasound for 5min at room temperature, a uniformly dispersed elastic conductive ink is finally obtained. The prepared elastic conductive ink with or without added adhesive is coated on different substrates, and the lap shear test is performed using the lap shear test method (GB / T7124-2008) at a tensile speed of 5mm / min (such as Figure 1 As shown in the figure, w / o represents the conductive ink sample without adhesive, and w / represents the conductive ink sample with adhesive). After testing, the results show that the addition of adhesive polybutyl acrylate effectively improves the adhesion of the conductive ink to different substrates.
[0066] Example 1
[0067] In this embodiment, a printable self-adhesive elastic conductive ink is provided, and the preparation method of the conductive ink is as follows: a thermoplastic elastomer solution is prepared according to a polymer mass fraction ratio of 19wt% (mass fraction of polystyrene-polyisoprene-polystyrene block copolymer in toluene solution), 0.4g of polystyrene-polyisoprene-polystyrene block copolymer is weighed, added to a toluene solvent, and magnetically stirred for 10h at room temperature at a speed of 600rpm to prepare a thermoplastic elastomer solution. 0.08g of ethylene-methyl methacrylate copolymer and 0.08g of surfactant KH570 are weighed, added to the thermoplastic elastomer solution, and magnetically stirred for 2h at room temperature at a speed of 600rpm, and then 0.16g of polybutyl acrylate is added, and magnetically stirred for 2h to obtain an elastomer mixed solution. The same elastomer mixed solutions A and B are prepared. The elastomer mixed solution A is poured into a polytetrafluoroethylene mold, and an elastic substrate is obtained after curing. Take 3.2g of gallium indium tin alloy, use a high-speed shear disperser (ScientzS10), and treat it at 10000r / min for 10min to obtain gallium indium tin alloy liquid microspheres with an average particle size of 6μm. Add the dispersed gallium indium tin alloy liquid microspheres to the above-prepared elastomer mixed solution B, and vortex disperse it for 10min at room temperature to obtain a gallium indium tin alloy liquid microsphere dispersion. Then take 1g of silver nanoparticles (average particle size 200nm) and add it to the above-prepared dispersion. At room temperature, vortex mix and disperse it for 20min to obtain a uniformly dispersed composite conductive filler dispersion. After defoaming in a water bath ultrasound for 5min at room temperature, a uniformly dispersed elastic conductive ink ( Figure 2 The prepared elastic conductive ink was coated on different substrates and the lap shear test was performed at a tensile speed of 5 mm / min using the lap shear test method (GB / T 7124-2008). The results showed that the elastic conductive ink had an adhesion of ~163.4 KPa on different substrates and an adhesion of 1090 KPa on wooden boards (such as Figure 3 The prepared elastic conductive ink was poured onto an elastic substrate. Taking advantage of the same solvent and polymer components, the solvent in the ink etched the bottom elastomeric substrate to obtain a tightly fitting elastic conductor. A uniaxial tensile test (GB / T 1040.3-2006) was performed at a speed of 10 mm / min. The resistance of the elastic conductor was recorded using a source meter (Keithley 2450) four-wire method (Kelvin measurement method). The real-time resistance of the elastic conductor under different tensile strains was obtained through the uniaxial tensile test. The resistance change calculation (R / R0, real-time resistance / initial resistance) showed that the resistance change was only 19.16 under 600% tensile strain, indicating that the elastic conductor has good mechanoelectric stability (such as Figure 4 Show).
[0068] Example 2
[0069] In this embodiment, a printable self-adhesive elastic conductive ink is provided, and the preparation method of the conductive ink is as follows: a thermoplastic elastomer solution is prepared according to a polymer mass fraction ratio of 19wt%, 0.6g of polystyrene-polyisoprene-polystyrene block copolymer is weighed, added to a toluene solvent, and magnetically stirred at room temperature at 600rpm for 10h. Weigh 0.12g of ethylene methyl methacrylate copolymer and 0.08g of surfactant KH570, add them to the thermoplastic elastomer solution, magnetically stir at room temperature at 600rpm for 2h, and then add 0.2g of polybutyl acrylate, and magnetically stir for 2h to obtain an elastomer mixed solution. Prepare the same elastomer mixed solutions A and B. The elastomer mixed solution A is poured into a polytetrafluoroethylene mold, and an elastic substrate is obtained after curing. Take 2.4g of gallium-indium alloy, and use a high-speed shear disperser to treat it at 10000r / min for 10min to obtain gallium-indium alloy liquid microspheres with an average particle size of 6μm. Add the dispersed gallium-indium alloy liquid microspheres to the prepared elastomer mixed solution B, and vortex disperse for 10 minutes at room temperature to obtain a gallium-indium alloy liquid microsphere dispersion. Then take 0.75g of micro-nano silver flakes (average particle size is 5μm) and add them to the prepared dispersion. Vortex mix and disperse for 20 minutes at room temperature to obtain a uniformly dispersed composite conductive filler dispersion. After defoaming in a water bath ultrasound for 5 minutes at room temperature, a uniformly dispersed elastic conductive ink is finally obtained. The elastic conductive ink is poured onto an elastic substrate and cured to obtain an elastic conductor. The conductive filler is evenly distributed in the conductor and has good dispersibility (such as Figure 5 The prepared elastic conductive ink was coated on different substrates, and the lap shear test was performed using the lap shear test method (GB / T 7124-2008) at a tensile speed of 5 mm / min. The results showed that the elastic conductive ink could achieve an adhesion of ~73.2 KPa on different substrates, and the adhesion on the wood board reached 580.8 KPa ( Figure 6 ). The conductive ink was cast onto the substrate prepared by the elastomer mixed solution A, and a tightly fitting elastic conductor was obtained after curing by taking advantage of the same solvent and polymer components. At room temperature, a uniaxial tensile test (GB / T1040.3-2006) was carried out at a tensile speed of 10 mm / min ( Figure 7 ) and 200% strain cyclic tensile test ( Figure 8 ), the resistance of the elastic conductor was recorded by the source meter four-wire method, and the real-time resistance of the elastic conductor under different tensile strains was obtained by uniaxial tensile test. The resistance change calculation (R / R0, real-time resistance / initial resistance) showed that the resistance change was only 7.25 under 1369.6% tensile strain. At the same time, the stress and resistance changes of the elastic conductor remained stable during 200 cycles of stretching and release under 200% tensile strain. These results show that the elastic conductor has good mechanical and electrical stability. With polyester knitted fabric ( Fig. 9) and cotton knitted fabrics ( Fig.10 ) as the substrate, using mask printing to prepare printed fabric electrodes. The field emission scanning electron microscope image shows the morphology of surface and edge diffusion and cross-sectional penetration morphology of the printed fabric electrode. It is calculated that the diffusion of the polyester knitted fabric electrode ink is only 142μm, with a diffusion rate of 2.8%; the penetration depth reaches 245μm. The diffusion of the cotton knitted fabric electrode ink is 232.7μm, with a diffusion rate of 4.6%; the penetration depth reaches 454μm. This shows that the conductive ink printed on the rough and porous knitted fabric has low diffusion and high permeability, and is closely integrated with the fabric substrate.
[0070] Example 3
[0071] In this embodiment, a printable self-adhesive elastic conductive ink is provided, and the preparation method of the conductive ink is as follows: a thermoplastic elastomer solution is prepared according to a polymer mass fraction ratio of 19wt%, 0.6g of polystyrene-polybutadiene-polystyrene block copolymer is weighed, added to a toluene solvent, and magnetically stirred for 10h at room temperature at a speed of 600rpm to prepare a thermoplastic elastomer solution. 0.12g of ethylene-vinyl acetate copolymer and 0.08g of surfactant KH570 are weighed, added to the thermoplastic elastomer solution, magnetically stirred for 2h at a speed of 600rpm at room temperature, and then 0.2g of polybutyl acrylate is added. After magnetic stirring for 2H, an elastomer mixed solution is obtained. The same elastomer mixed solutions A and B are prepared. The elastomer mixed solution A is poured into a polytetrafluoroethylene mold, and an elastic substrate is obtained after curing. Take 3.2g of gallium-indium alloy, use a high-speed shear disperser, and treat it at 10000r / min for 10min to obtain gallium-indium alloy liquid microspheres with an average particle size of 6μm. Add the dispersed gallium-indium alloy liquid microspheres to the prepared elastomer mixed solution B, and vortex disperse for 10 minutes at room temperature to obtain a gallium-indium alloy liquid microsphere dispersion. Then take 1g of micro-nano silver flakes (average particle size is 10μm) and add them to the prepared dispersion. Vortex mix and disperse for 20 minutes at room temperature to obtain a uniformly dispersed mixed conductive filler dispersion. Defoam in a water bath ultrasound for 5 minutes at room temperature to finally obtain a uniformly dispersed elastic conductive ink. The prepared elastic conductive ink is coated on different substrates, and the lap shear test method (GB / T7124-2008) is used to perform a lap shear test at a tensile speed of 5mm / min. The results show that the elastic conductive ink can achieve an adhesion of ~69.3KPa on different substrates, and the adhesion on the wooden board can reach 438.8KPa ( Fig.11 ). The conductive ink is poured onto the prepared elastic substrate, and a tightly fitting elastic conductor is obtained after curing by taking advantage of the same solvent and polymer components. At room temperature, a uniaxial tensile test (GB / T 1040.3-2006) is carried out at a tensile speed of 10 mm / min ( Fig.12), the resistance of the elastic conductor was recorded by the source meter four-wire method, and the real-time resistance of the elastic conductor under different tensile strains was obtained by uniaxial tensile test. The resistance change calculation (R / R0, real-time resistance / initial resistance) showed that the resistance change of the elastic conductor under 1000% tensile strain was only 6.68, which had good mechanoelectric stability. The printed fabric electrodes were prepared by mask printing using weft plain knitted polyester fabric and plain woven cotton fabric as substrates. The morphology of the surface and edge diffusion and the cross-sectional penetration morphology of the fabric electrode were observed and analyzed using optical microscopy and field emission scanning electron microscopy. It was calculated that the diffusion distance of the polyester knitted fabric electrode ink was only 10μm, the diffusion rate was 0.2%, and the penetration depth reached 200.4μm. The diffusion distance of the plain woven cotton fabric electrode ink was 236.5μm, the diffusion rate was 4.73%, and the penetration depth reached 186μm. This shows that the conductive ink printed on the rough and porous knitted fabric has lower diffusion and higher permeability, and can be tightly combined with the fabric substrate, which helps to improve the mechano-electrical stability of the fabric electrode.
[0072] Example 4
[0073] In this embodiment, a printable self-adhesive elastic conductive ink is provided, and the preparation method of the conductive ink is as follows: a thermoplastic elastomer solution is prepared according to a polymer mass fraction ratio of 19wt%, 0.6g of polystyrene-polyisoprene-styrene block copolymer is weighed, added to a toluene solvent, and magnetically stirred for 10h at room temperature at a speed of 600rpm to prepare a thermoplastic elastomer solution. Weigh 0.08g of ethylene-vinyl acetate copolymer and 0.08g of surfactant KH570, add them to the thermoplastic elastomer solution, magnetically stir for 2h at a speed of 600rpm at room temperature, and then add 0.16g of polybutyl acrylate, and magnetically stir for 2h to obtain an elastomer mixed solution. Prepare the same elastomer solutions A and B. The elastomer mixed solution A is poured into a polytetrafluoroethylene mold, and an elastic substrate is obtained after curing. Take 3.2g of gallium indium tin alloy, and use a high-speed shear disperser to treat it at 10000r / min for 10min to obtain gallium indium tin alloy liquid microspheres with an average particle size of 6μm. Add the dispersed gallium indium tin alloy liquid microspheres to the prepared elastomer mixed solution B, and vortex disperse for 10 minutes at room temperature to obtain a gallium indium tin alloy liquid microsphere dispersion. Then take 1g of silver nanowires (average diameter 60nm) and add them to the prepared dispersion. Vortex mix and disperse for 20 minutes at room temperature to obtain a uniformly dispersed composite conductive filler dispersion. Defoam in a water bath ultrasound for 5 minutes at room temperature to finally obtain a uniformly dispersed elastic conductive ink. The prepared elastic conductive ink is coated on different substrates, and a lap shear test is performed using the lap shear test method (GB / T7124-2008) at a tensile speed of 5mm / min. The results show that the elastic conductive ink can achieve an adhesion of ~83.1KPa on different substrates, and the adhesion on the wooden board reaches 540.3KPa ( Fig.13 ). The conductive ink is poured onto the prepared elastomer substrate, and a tightly fitting elastic conductor is obtained after curing by taking advantage of the same solvent and polymer components. At room temperature, a uniaxial tensile test (GB / T 1040.3-2006) is carried out at a tensile speed of 10 mm / min ( Fig.14), the resistance of the elastic conductor was recorded by the source meter four-wire method, and the real-time resistance of the elastic conductor under different tensile strains was obtained by uniaxial tensile test. The resistance change calculation (R / R0, real-time resistance / initial resistance) showed that the resistance change of the elastic conductor under 1294.1% tensile strain was only 8.72, which had good mechanoelectric stability. Polyester knitted fabric (camouflage cloth) and non-woven polypropylene non-woven fabric were used as substrates, and the printed fabric electrodes were prepared by mask printing. The morphology of the surface and edge diffusion and the cross-sectional penetration morphology of the printed fabric electrode were observed by optical microscopy and field emission scanning electron microscopy. It was calculated that the ink diffusion distance of the polyester knitted fabric (camouflage cloth) electrode was only 9.6μm, and the diffusion rate was 0.192%; the penetration depth reached 218.6μm. The ink diffusion distance of the non-woven polypropylene non-woven fabric electrode was 181μm, and the diffusion rate was 3.6%; the penetration depth reached 241.8μm. This shows that the conductive ink printed on knitted fabrics with larger pore sizes has low diffusion and high permeability, and can be tightly bonded to the fabric substrate, which helps to improve the mechanical-electrical stability of the fabric electrode.
[0074] Example 5
[0075] In this embodiment, a printable self-adhesive elastic conductive ink is provided, and the preparation method of the conductive ink is as follows: a thermoplastic elastomer solution is prepared according to a polymer mass fraction ratio of 19wt%, 0.4g of polystyrene-ethylene-butylene-polystyrene block copolymer is weighed, added to a toluene solvent, and magnetically stirred at room temperature at 600rpm for 10h to prepare a thermoplastic elastomer solution. 0.08g of ethylene-vinyl acetate copolymer and 0.08g of surfactant KH570 are weighed, added to the thermoplastic elastomer solution, magnetically stirred at room temperature at 600rpm for 2h, and then 0.16g of polybutyl acrylate is added, and magnetically stirred for 2h to obtain an elastomer mixed solution. 3.2g of gallium indium tin alloy is taken, and after being treated at 12000r / min for 10min using a high-speed shear disperser, gallium indium tin alloy liquid microspheres with an average particle size of 4μm are obtained. The dispersed gallium indium tin alloy liquid microspheres were added to the prepared elastomer mixed solution, and vortexed and dispersed for 10 minutes at room temperature to obtain a gallium indium tin alloy liquid microsphere dispersion. Then 1g of micro-nano silver flakes (average diameter particle size 5μm) were added to the prepared dispersion, and vortexed and dispersed for 20 minutes at room temperature to obtain a uniformly dispersed composite conductive filler dispersion. After defoaming in a water bath ultrasound for 5 minutes at room temperature, a uniformly dispersed elastic conductive ink was finally obtained. Dispensing printing (Scientific 3) and mask printing were used on a polyimide substrate ( Fig.15 ), fabrics of different structures (plain weave, twill weave, plain weft knitting, 2×2 double thread knitting) ( Fig.16) can be printed on and prepared with high-precision printed circuits and electrodes. Using 2×2 double-thread knitted fabric and twill woven fabric as the substrate, printed fabric electrodes were prepared by mask printing. The morphology of surface and edge diffusion and cross-sectional penetration morphology of printed fabric electrodes were observed using optical microscopy and field emission scanning electron microscopy. It was calculated that the ink diffusion distance of 2×2 double-thread knitted fabric electrode was only 6.2μm, and the diffusion rate was 0.124%; the penetration depth reached 319.2μm. The ink diffusion of twill woven fabric electrode was 234μm, with a diffusion rate of 4.68%; the penetration depth reached 251.3μm. This shows that the conductive ink has low diffusivity and high permeability when printed on knitted fabrics with more pores, and can be tightly combined with the fabric substrate, which helps to improve the mechanical-electrical stability of the fabric electrode.
Claims
1. An elastic conductive ink, characterized in that: By weight, the components include: The thermoplastic elastomer is a block copolymer; the interfacial enhancer is a surfactant and a polyester elastomer composite; The adhesive is polyacrylate; The block copolymer includes one or more of the triblock copolymers; The conductive filler is composed of rigid conductive filler and flexible conductive filler.
2. The elastic conductive ink according to claim 1, characterized in that: The mass ratio of the surfactant to the polyester elastomer in the interface enhancer is 1:10 to 5:1; The triblock copolymer includes one or more of polystyrene-polybutadiene-polystyrene block copolymer, polystyrene-polyisoprene-polystyrene block copolymer, and polystyrene-ethylene-butylene-polystyrene block copolymer; The polyacrylate adhesive includes one or more of polyethyl acrylate, polybutyl acrylate, and poly(butyl acrylate-styrene); The surfactant includes one or more of a silane coupling agent and a titanate coupling agent; The polyester elastomer includes one or more of ethylene-vinyl acetate copolymer and ethylene-methyl methacrylate copolymer; the vinyl acetate content of the ethylene-vinyl acetate copolymer is 40% to 70%; the methyl methacrylate content of the ethylene-methyl methacrylate copolymer is 10% to 20%; The rigid conductive filler includes one or more of metal micro-nano particles, metal nanowires, metal micro-nano sheets, carbon-based micro-nano conductive materials, modified carbon-based or metal micro-nano conductive materials, and transition metal micro-nano conductive materials; the flexible conductive filler includes one or more of ionic liquids, liquid metal gallium, liquid alloy gallium-indium alloy, gallium-indium-tin alloy, and liquid metal modifiers.
3. The elastic conductive ink according to claim 2, characterized in that: The mass ratio of the rigid conductive filler to the flexible conductive filler is 10:20 to 10:40; The average particle size of the rigid conductive filler is 0.1μm to 100μm; the average particle size of the flexible conductive filler is 0.1μm to 100μm; the metal nanoparticles include one or more of gold micro-nanoparticles, silver micro-nanoparticles, and copper micro-nanoparticles; the metal nanowires include one or more of gold nanowires, silver nanowires, and copper nanowires; the metal micro-nanosheets include one or more of gold micro-nanosheets, silver micro-nanosheets, and copper micro-nanosheets; the carbon-based micro-nano conductive materials include one or more of carbon black micro-nano particles, carbon nanotubes, graphene, and MXene.
4. A printed and / or printed material, characterized in that The material is a printing material and / or a printed material based on the elastic conductive ink according to claim 1.
5. The printed and / or printed material according to claim 4, characterized in that: The substrate used for the printing material and / or the printed material is a smooth substrate, or a rough and / or porous substrate.
6. An elastic conductor, characterized in that: The elastic conductor comprises the elastic conductive ink of claim 1 and an elastic substrate.
7. A method for preparing an elastic conductive ink, comprising: (1) mixing a thermoplastic elastomer, an interfacial enhancer, an adhesive, and a solvent to obtain a mixed solution; (2) Dispersing the conductive filler in the mixed solution of step (1), defoaming, and obtaining elastic conductive ink.
8. The preparation method according to claim 7, characterized in that: The solvent includes one or more of water, acetone, toluene, chlorobenzene, xylene, tetrahydrofuran, N,N-dimethylformamide, dimethyl sulfoxide, and chloroform.
9. The preparation method according to claim 7, characterized in that: The mass percentage of the thermoplastic elastomer in the mixed solution in step (1) is 5% to 30%; The step (2) of dispersing the conductive filler in the mixed solution of step (1) is specifically as follows: firstly dispersing the flexible conductive filler in the mixed solution of step (1), and then adding the rigid conductive filler for dispersion; The defoaming in step (2) is ultrasonic defoaming, wherein the defoaming ultrasonic time is 1 min to 30 min and the power is 100 W to 300 W.
10. An application of the elastic conductive ink according to claim 1 in the fields of printing / printed electronic devices, electronic fabrics, electronic skin, human health monitoring, soft robots, human-computer interaction, information transmission, and energy collection and storage.